The clinical implication of lymph nodes micrometastases and isolated tumor cells in patients with cervical cancer: A systematic review. (October 2019) - Delomenie, Myriam; Bonsang-Kitzis, Hélène; Bats, Anne-Sophie; Ngo, Charlotte; Balaya, Vincent; Xuan, Huyen Thu Nguyen; Koual, Meriem; Mathevet, Patrice; Lecuru, Fabrice
Highlights: We review the diagnostic approaches to lymph nodes involvement in cervical cancer. We present the possible definitions for lymph nodes micrometastases (MMs) and isolated tumor cells (ITCs). We describe the data regarding prognosis and treatment of patients diagnosed with cervical carcinoma with MMs or ITCs. Abstract: Lymph node macroscopic involvement in cervical cancer is a well-known prognostic factor, allows the gynecologic-oncologist to identify women at increased risk for recurrence. Since the development of sentinel node biopsy, micrometastases (MMs) and Isolated Tumor Cells (ICTs) have been increasingly identified in cervical cancer, however their prognostic value and treatment are still controversial. We reviewed the literature (MEDLINE and EMBASE database analysis) from inception up to January 2019, concerning the incidence of lymph nodes MMs and ITCs in cervical cancer, their controversial histologic and molecular biology definition, their anatomic distribution, the role of frozen section and the prognostic value and treatment options for women diagnosed with lymph nodes MMs/ITCs.